Mechanical properties of polymer-infiltrated fluorapatite glass ceramics fabricated from clam shell and soda lime silicate glass - Kul, Esra; Matori, Khamirul Amin; Karadeniz, Sukran; Arslan, Ersin; Ertugrul, Mehmet (Revista de Chimie, 2023)
Can polymer-infiltrated florapatite glass ceramic produced from waste materials, such as clam shell and soda lime silicate glass, be used in prosthetic rehabilitation? The purpose of this study is to investigate the effect of Si/Ca ratio on the mechanical properties of Nb-Bi-Ce doped polymer-infiltrated fluorapatite ceramic networks (PICNs) produced from clam shell (CS) and soda lime silicate (SLS) glass by conventional melt-quench technique, used as a dental ceramic. PICNs comprising Si/Ca at four different weight percentage ratios: 1.27% (PICN-1), 2.15% (PICN-2), 4.12% (PICN-3) and 12.6% (PICN-4) were prepared (n=10). The powder mixtures in four different ratios were compressed in a rectangular prism shaped mold and subjected to equal pressure from all sides in a cold isostatic press, followed by heat treatment at 750C for 3 h. Then complete vacuum infiltration was done with a polymer mixture then low temperature firing was applied leading to the formation of the PICNs. Wear behavior and 3-point bending properties were evaluated and specimens were analyzed using scanning electron microscopy (SEM). The friction and wear properties were determined by means of a pin-on-disk tribotester. Since the flexural strength test did not show normal distribution, Kruskal Wallis test was performed in independent groups, p[0.05. There is a significant difference of flexural strength values between the groups (p=0.032), it was determined that the difference was between the PICN-1 and PICN-4 groups (p=0.037). In the analysis of wear scar, abrasion grooves were also observed. The results of this study showed that high Ca and Si content in CS and SLS glass, respectively, encourages the use of waste materials in the production of PICNs intended to be used in prosthetic rehabilitation. The composition of PICNs produced from waste materials affected flexural strength and wear behavior. Increasing the Si/Ca ratio was found to support the mechanical properties of experimental PICN and that experimental PICNs can be considered as high potential candidates for dental applications.